OS4.4 Interventions to help support caregivers of people with a brain or spinal cord tumour - a Cochrane systematic review. (19th September 2018) - Boele, F W; Rooney, A G; Bulbeck, H; Sherwood, P R
Abstract: Background: Family caregiving in neuro-oncology is linked to considerable burden and distress. Meeting the support needs of family caregivers is critical to maintain their emotional and physical health, enabling them to continue their caregiving activities for longer. Although support for caregivers is becoming more widely available, large-scale implementation is hindered by a lack of high-quality evidence for its effectiveness in the neuro-oncology caregiver population. We performed a Cochrane systematic review to assess the effectiveness of supportive interventions at improving the wellbeing of caregivers of people with a brain or spinal cord tumour. Material and Methods: In March 2017, we searched for studies in CENTRAL, MEDLINE and Embase. We also handsearched relevant conference abstracts published (past 5 years), publications in the two main journals in the field (past year), searched for ongoing trials via ClinicalTrials.gov, and contacted research groups in this field. We included all randomised studies where caregivers of neuro-oncology patients constituted >20% of the sample and which evaluated changes in caregiver wellbeing following any supportive intervention. Two review authors independently selected studies and carried out risk of bias assessments. We aimed to extract data on the outcomes of psychological distress, burden, mastery, quality of patient-caregiver relationship, quality of life, and physical functioning. Results: In total, 1666 records were identified, of which 122 were reviewed in full-text. We could include five studies (four ongoing trials were also identified). Three interventions focused on patient-caregiver dyads and two were aimed specifically at the caregiver. Heterogeneity of populations and methodologies precluded meta-analysis. Risk of bias varied, but all studies included only small numbers of neuro-oncology caregivers (n range= 13 - 56). Some evidence was found for positive effects of caregiver support on psychological distress and mastery (GRADE quality of evidence: low to very low). No studies reported significant effects on caregiver burden, quality of life, or quality of patient-caregiver relationship (GRADE quality of evidence: low to very low). Caregiver physical functioning was not assessed in the studies. Conclusion: The five small-scale studies included employed different methodologies across different populations, with a low quality of evidence overall. It is not currently possible to draw reliable conclusions regarding the effectiveness of supportive interventions aimed at improving neuro-oncology caregiver wellbeing. More high-quality research is needed on support for family caregivers of patients diagnosed with a brain or spinal cord tumour.